A Clinical Study of Fetal Outcome in Cases of Nuchal Cord - Begum, AA; Sultana, H; Hasan, R; Ahmed, M (Journal of Armed Forces Medical College, Bangladesh, 2011)
Introduction: The umbilical cord around the neck of the fetus at the time of birth is nuchal cord. Objectives : To study the perinatal events and fetal outcome in cases with nuchal cord and formulate a plan for safe delivery. Methods: This cross sectional prospective study of 152 cases of nuchal cord (out of 1646 deliveries) was carried out in department of Obstetrics and Gynaecology of a Combined Military Hospital of Bangladesh during the period of two years. The nuchal cords were classified as tight coils or loose coils. Apgar score at 1 and 5 minutes after birth were recorded. Birth weight and sex of all babies were noted. Cord length was measured and considered as long (>70 cm) and short (<35 cm). Results: Out of 152 cases 128 (84.21%) had normal vaginal delivery, 3 (1.97%) cases had instrumental delivery, 21 (13.82%) cases underwent caesarean section and fetal distress was the main indication (16 out of 21). Only 22 (14.47%) of fetuses manifested fetal heart rate variation mostly variable deceleration (10 out of 22). Neonates born with tight nuchal cord had low Apgar score in one minute in comparison to loose (p<0.05), whereas significantly low Apgar score after 5 minutes was observed in babies born with multiple nuchal cord. Conclusion: The presence of a nuchal cord per se is not found to be an indication of operative delivery. However, such patients require close monitoring during labour, preferably by continuous electronic fetal heart rate monitoring as well as strict maintenance of partogram. Key words: Nuchal cord; normal delivery; caesarean section; fetal outcome DOI: http://dx.doi.org/10.3329/jafmc.v7i1.8622 JAFMC Bangladesh. Vol 7, No 1 (June) 2011; 25-27